The Use of Free Writing Technique to Developed Students’ Writing Skill at UIN Prof. K.H Saifuddin Zuhri Purwokerto: Students’ Perception - Nasichah, Alfi Hulwatun (International Journal of Instructions and Language Studies, 2024)
In this era, developing writing skills is crucial for the students. Because they can make any types of writing text that will be necessary for their future career. In fact, every student and teacher in a writing class may be facing unique challenges. A rangesof writing strategies are necessary for an effective teaching and learning process. Without the appropriate writing strategies, the students will always face the difficulties in their learning process. The free writing technique is one of the appropriate instructional strategies for writing. This study aims to find out the students' perception about the use of free writing technique. The data were collected through questionnaires which were distributed to 33 English students of UIN Prof.K.H Saifuddin Zuhri Purwokerto. This research used quantitative method to describe the research result. According to the data, the majority of students believe that by including the free writing technique into their learning process, they may improve their writing skills. Keywords: Free Writing;Writing Skill; Student’s Perception